PENGARUH MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA POWTOON TERHADAP MINAT DAN HASIL BELAJAR SISWA PADA MATERI LAJU REAKSI (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of the Problem Based Learning (PBL) model assisted by Powtoon media on students’ learning interest and learning outcomes in reaction rate material. The study was conducted at SMA Negeri 1 Raya using a quasi-experimental design, namely the Pretest-Posttest Control Group Design, involving an experimental class and a control class. The samples were selected through random sampling, with each class consisting of 36 students.The research instruments included a multiple-choice test to measure students’ chemistry learning outcomes and a questionnaire to assess students’ learning interest. All instruments were validated by expert validators prior to use. Data analysis showed that the average increase in students’ learning outcomes in the experimental class was 76.01%, higher than the control class at 58.55%. Similarly, students’ learning interest in the experimental class reached an average of 71.61%, compared to 54.33% in the control class.Hypothesis testing using the right-tailed t-test revealed a significance value of 0.000 < α (0.05) for both learning interest and learning outcomes. This indicates that the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. Therefore, it can be concluded that the use of the PBL model assisted by Powtoon media has a significant effect on improving students’ learning interest and learning outcomes compared to conventional learning on reaction rate material.